HUBUNGAN MOTIVASI DENGAN SELF-REGULATED LEARNING PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - Balyanan, Tuti Kalsum; Taihuttu, Yuniasih MJ; Ariwicaksono, Stefanus C (PAMERI, 2024)
The first year of college is the most challenging period for students because of new situations, such as lecture systems, learning materials, and environments that are distinct from high school, so adaptability is necessary when someone enters college. Self-regulated learning is an activity where the student can freely determine and manage the learning process needed by the student and is related to three aspects of academic activities, namely metacognition, motivation, and behaviour. The purpose of this study is to determine the relationship between motivation and self-regulated learning in students of the Faculty of Medicine, Pattimura University. This study is a quantitative analytical research with a cross-sectional design using a total sampling technique with a total of 672 students of the Faculty of Medicine, Pattimura University, from the class of 2018-2021 in September-October 2022. The results of the study showed that from the 672 respondents, the percentages of the respondents who had high motivation and who had high self-regulated learning were 81.4% and 61%, respectively. Data analysis using the Fisher exact test showed the significance of the value of p ≤ 0,001. Thus, there is a significant relationship between motivation and self-regulated learning in students of the Faculty of Medicine Pattimura University